A relação família-escola no contexto da educação do campo no município de Serra do Mel/RN: desafios e perspectivas - Silva, Marina Cintya Alves da (Universidade Federal Rural do Semi-Árido, 2019)
The objective of this monographic work was to investigate the challenges and perspectives inherent to the family-school relationship in the context of rural education, in schools located in the municipality of Serra do Mel / RN, with the aim of identifying and understanding the challenges and perspectives concerning this relationship. The specific objectives were to know aspects (social, economic and geographic) about the existence of the students’ families of the schools approached in this research; to investigate the process of parents' engagement in the direct formation of their children and to analyze the actions of schools to relate with families, identifying the challenges and perspectives. This work was based on the recognition of the need to research that relationship, which impacts individuals’ lives, positively or negatively. The research methods involved bibliographical, documental and field research. The research accomplished reached out satisfactory results, like the relevant discussion stimulated by this research about the relation school-family, considering several reports and theories about the theme, adding positively to improve that relationship, with appointments and suggestions about the theme.
Monografia
Keywords: Relação; Escola; Família; Relation; School; Family; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL